Achieving sustainable production and consumption of virgin plastic polymers - Grabiel, Tim; Gammage, Tom; Perry, Clare; Dixon, Christina (Frontiers in Marine Science, 2022)
The United Nations Environment Assembly (UNEA) recently adopted a resolution with a mandate to negotiate a new international legally binding instrument (a treaty) on plastic pollution. The mandate includes the need to ‘prevent’ as well as ‘reduce’ and ‘eliminate’ plastic pollution through a ‘comprehensive approach that addresses the full life cycle of plastic’. Unsustainable production and consumption of virgin (primary) plastic polymers represents the single greatest threat to preventing plastic pollution and risks undermining the incoming treaty. However, current discussions on a global plastics treaty overlook upstream measures that address virgin plastic production and consumption, focusing instead on midstream and downstream measures on product design and waste management. This article presents the justification for and benefits of a stepwise approach for controlling virgin plastic production and consumption internationally, inspired by the Montreal Protocol on Substances that Deplete the Ozone Layer;